Relationship between thyroid nodules and iodine nutritional status, thyroglobulin (Tg), and other influencing factors: a 1:1 matched case-control study - Lin, Qingying; Wang, Lijin; Chen, Diqun; Wu, Jiani; Lan, Ying; Jin, Qingdong; Chen, Yanqing; Chen, Zhihui; Wang, Muhua (Frontiers in Endocrinology, 2025)
BackgroundAn increasing trend in the prevalence of thyroid nodules has highlighted whether thyroid nodules are related to the level of iodine nutrition.MethodsThis 1:1 matched case-control study was conducted to investigate whether thyroid nodules are related to the level of iodine nutrition. The residents who had lived there for more than 5 years with thyroid nodules composed the case group. All the subjects completed questionnaires, and blood and urine samples were collected.ResultsThe MUI of the case group in areas with more than adequate iodine intake was lower than that of the control group (P<0.05); only the level of Tg in the case group was higher than that in the control group in areas with adequate iodine intake (P<0.05). The conditional logistic regression model revealed that there were significant correlations between a history of thyroid disorders, Tg, TgAb, and thyroid nodules.ConclusionsIn areas with more than adequate iodine intake, a slight increase in urinary iodine may be associated with a lower risk of thyroid nodules. A history of thyroid disorders and increased Tg and TgAb levels are risk factors for thyroid nodules. Tg level detection has certain diagnostic value in distinguishing thyroid nodules.